PENERAPAN TEKNIK ONTOLOGY UNTUK PENCARIAN DATA AKADEMIK - Jemmy Edwin Bororing; Fatsyahrina Fitriastuti (Universitas Janabadra, 2017)
Semantic Web is a network that is able to understand not only the meaning of a word and a concept, but also a logical relationship between the two, so that a website can generate the appropriate information and desired by visitors to the website. The language used in support of the vision of the semantic web is the Resource Description Framework (RDF) / Web Ontology Language (OWL). RDF / OWL capabilities and its facilities capable of being used to represent the meaning of terms in the web to be processed in the machine. Therefore, the research discusses the development of a model for a knowledge management system with the research domain, namely the Academic Information Systems, Faculty of Engineering, University Janabadra. Model form of web- based prototype. This web prototypes using semantic web technologies with application of ontology. Ontology built implemented using Protege 3.4.8. besides it is also used Java Development Kit (JDK) and the Command Prompt as an emulator prototype web. As for seeing the display prototypes use semantic web-bank. Keywords : Knowledge management system, semantic web, ontology, protégé, semantic-bank